Effects of Fruits of Lapsi (Nepali Hog Plum) Choerospondias axillaris (roxb.) b.l.Burtt & a.w.Hill on Some Blood Parameters of Major Carp rohu Labeo rohita(H) During Intensive Aquaculture - Shakya, Shubha Ratna; Labh, Shyam Narayan (Nepal Journal of Science and Technology, 2020)
The complete blood cell count (CBC) is an important and powerful diagnostic tool to monitor the health status of fish in response to changes related to nutrition, water quality, and disease in response to therapy.Thus, the present study was about to know the effect of lapsi fruit pulp (Choerospondias axillaris) on some blood parameters in the fingerlings of rohu Labeo rohita cultured in Corona of Agriculture Hatchery farm, Chitwan, Nepal. Altogether eighteen hapas made of heavy-duty nylon net (1.5m3) were kept and placed inside the pond, distributed linearly, and then 270 fingerlings (@15 fishes/ hapa) were kept distributed randomly. Six practical diets like T1 (0.0 g kg-1), T2 (0.1 g kg-1), T3 (0.2 g kg-1), T4 (0.4 g kg-1), T5 (0.8 g kg-1) and T6 (1.6 g kg-1) were prepared. Feed containing 40% protein was supplemented with the ethanol extract of lapsi fruits. At the end of 90 days of the feeding trial, a significant difference (P< 0.05) in blood parameters were observed between the treated and control diet-fed groups. Hemoglobin (Hb), white blood cells (WBCs), red blood cells (RBCs), packed cell volume (PCV), and other erythrocyte indices were recorded higher in the treated groups. RBC, WBC, Hct, and Hb were found significantly higher in the T4 (0.4 %) diet-fed group. The study showed a minimum of 0.4 % (0.4g kg-1) lapsi fruit extract needed in fish feeds to increase blood parameters to enhance growth and immunity.